Screening of novel β-carotene hydroxylases for the production of β-cryptoxanthin and zeaxanthin and the impact of enzyme localization and crowding on their production in Yarrowia lipolytica - Soldat, Mladen; Markuš, Tadej; Magdevska, Vasilka; Kavšček, Martin; Kruis, Aleksander Johannes; Horvat, Jaka; Kosec, Gregor; Fujs, Štefan; Petrovič, Uroš (Microbial cell factories, 2024)
Zeaxanthin, a vital dietary carotenoid, is naturally synthesized by plants, microalgae, and certain microorganisms. Large-scale zeaxanthin production can be achieved through plant extraction, chemical synthesis, or microbial fermentation. The environmental and health implications of the first two methods have made microbial fermentation an appealing alternative for natural zeaxanthin production despite the challenges in scaling up the bioprocess. An intermediate between β-carotene and zeaxanthin, β-cryptoxanthin, is found only in specific fruits and vegetables and has several important functions for human health. The low concentration of β-cryptoxanthin in these sources results in low extraction yields, making biotechnological production a promising alternative for achieving higher yields. Currently, there is no industrially relevant microbial fermentation process for β-cryptoxanthin production, primarily due to the lack of identified enzymes that specifically convert β-carotene to β-cryptoxanthin without further conversion to zeaxanthin. In this study, we used genetic engineering to leverage the oleaginous yeast Yarrowia lipolytica as a bio-factory for zeaxanthin and β-cryptoxanthin production. We screened 22 β-carotene hydroxylases and identified eight novel enzymes with β-carotene hydroxylating activity: six producing zeaxanthin and two producing only β-cryptoxanthin. By introducing the β-carotene hydroxylase from the bacterium Chondromyces crocatus (CcBCH), a β-cryptoxanthin titer of 24 ± 6 mg/L was achieved, representing the highest reported titer of sole β-cryptoxanthin in Y. lipolytica to date. By targeting zeaxanthin-producing β-carotene hydroxylase to the endoplasmic reticulum and peroxisomes, we increased the production of zeaxanthin by 54% and 66%, respectively, compared to untargeted enzyme. The highest zeaxanthin titer of 412 ± 34 mg/L was achieved by targeting β-carotene hydroxylases to peroxisomes. In addition, by constructing multienzyme scaffold-free complexes with short peptide tags RIDD and RIAD, we observed a 39% increase in the zeaxanthin titer and a 28% increase in the conversion rate compared to the strain expressing unmodified enzyme. The zeaxanthin titers obtained in this study are not the highest reported; however, our goal was to demonstrate that specific approaches can enhance both titer and conversion rate, rather than to achieve the maximum titer. These findings underscore the potential of Y. lipolytica as a promising platform for carotenoid production and provide a foundation for future research, where further optimization is required to maximize production.